2017
DOI: 10.1155/2017/7521831
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Self-Medication in Dermatology in Togo

Abstract: Objective This study aimed to determine the prevalence of and factors associated with self-medication in dermatology in Lomé, Togo. Methods We conducted an analytical cross-sectional study from February to April 2016 in 2 dermatology departments in Lomé. Univariate and multivariate logistic regression models were carried out to identify possible factors associated with self-medication. Results A total of 711 patients were included in the study. The mean age (±SD) of the patients was 26.6 ± 6.9 years and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 9 publications
(10 reference statements)
10
34
1
1
Order By: Relevance
“…The consequence of this is the use of over the counter remedies by patients. A similar use of remedies by majority of patients prior to clinic attendance has been documented in other studies (Kombate et al, 2017;Mustafa & Rohra, 2017). Most of the patients in this study had an inflammatory disease.…”
Section: T a B L E 3 Test Of Significance Between Use Of Herbs And Vasupporting
confidence: 85%
See 3 more Smart Citations
“…The consequence of this is the use of over the counter remedies by patients. A similar use of remedies by majority of patients prior to clinic attendance has been documented in other studies (Kombate et al, 2017;Mustafa & Rohra, 2017). Most of the patients in this study had an inflammatory disease.…”
Section: T a B L E 3 Test Of Significance Between Use Of Herbs And Vasupporting
confidence: 85%
“…The reports from this study are at variance with that by Lindberg where the more female gender was found to be more likely to use herbal medications (Olaitan, ). Kombate et al () in Lome found a high level of education to be protective against the use of herbal medications just as in this study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Selfmedication with both prescription and over-the-counter drugs is a common problem in developing countries, unlike in developed countries, where self-medication usually involves only over-the-counter drugs . [45][46][47][48][49] The incidence of selfmedication varies in developing countries, ranging from 12.4 to 91.3%. In our patient population 43% took self-prescribed over-the-counter drugs.…”
Section: Original Articlementioning
confidence: 99%